Pengaruh Budaya Organisasi Terhadap Kepuasan Kerja Perawat di Ruang Rawat Inap Rumah Sakit Mitra Medika Tanjung Mulia Kota Medan - Friskila Hotnaria; Arifah Devi Fitriani; Asyiah Simanjorang (Ilmu Bersama Center, 2022)
Nurse job satisfaction tends to be influenced by the prevailing hospital organizational culture. This study aims to analyze the influence of organizational culture on the job satisfaction of nurses in the inpatient room at Mitra Medika Tanjung Mulia Hospital, Medan City. This type of research is quantitative with a cross sectional study design carried out from September to October 2021. The research population is 84 nurses in the inpatient room. The sampling technique was total sampling with a total sample of 84 people. Data analysis consisted of univariate analysis, bivariate with Chi-Square, multivariate with logistic regression. The results of the univariate analysis showed that most of the respondents were aged 36-45 years 52 (61.9%), female 64 (76.2%), and had a D3 Nursing education level 69 (65.71%). bivariate analysis shows that there is an influence of organizational culture, there is an influence of organizational culture, there is an influence of organizational culture, there is an influence of organizational culture, there is an influence of organizational culture, and there is an influence of organizational culture on the stability aspect of nurses' job satisfaction. multivariate analysis showed that the most influential variable on nurse job satisfaction was the result orientation variable. It is recommended to hospital management to provide nurses with training so that nurses can work according to the targets that have been set.